Belarus : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
This paper first discusses recent economic developments through the first half of 2000, and then, provides an assessment of vulnerabilities in the Belarusian banking system. Dollarization in Belarus is also discussed. In this paper, the current business environment and the existing obstacles to reach these objectives are described. Agriculture plays a key role in the Belarusian economy. Finally, the lack of progress in agricultural reform, especially with respect to land reform and the development of private sector farming, is described.